Development of cycling performance variables and durability in female and male national team cyclists: From junior to senior - Almquist, N. W.; Hansen, J.; Rønnestad, B. R. (Medicine & Science in Sports & Exercise, 2023)
Aim This study investigated the development of power profiles and performance-related measures from the junior level (<19 yr) via U23 (19-23 yr) to senior level (>23 yr) in 19 female and 100 male Norwegian national team cyclists.